Towards Digital Coaching: Opportunities , Personalization and Challenges - El Houcine El Bazi et al. (International Journal of Scientific Research and Innovative Studies, 2025)
This study underscores the growing demand for digital coaching as a real response to evolving personal and market needs. This transformative shift has fostered a synergy between human intuition and technological innovation. This, in other words, reshape the future of coaching by unlocking new opportunities for growth and fulfilment for both coaches and coachees. Moreover, the flexibility by removing geographical barriers through online access to coaching materials and sessions reinforces hybrid model thatensures a personalised and comprehensive coaching experience. This, in return, attracts a broader user audience and contributing to the overall coaching market.